El computador y su influencia en la organización y administración de la educación en la Unidad Educativa “Eugenio Espejo” de la Ciudad de Babahoyo 2016-2017 - Laina Bayas, Erica Paola (2016)
The present research work entitled " THE COMPUTER AND ITS INFLUENCE IN THE ORGANIZATION AND ADMINISTRATION OF EDUCATION IN THE EDUCATIONAL UNIT “EUGENIO MIRROR” OF THE CITY OF BABAHOYO PROVINCE OF THE RIVERS Has Determine the aspects in which the use of the computer improves the processes of organization and administration of education in the Educational Unit “Eugenio Espejo” of the city of Babahoyo Province Los Ríos. Field research was used, Descriptive-Exploratory with the Deductive Method Synthetic Analysis and its respective survey applied to teachers and administrative staff with a sample of 60 participants. The results of the research identified the variables that intervene in the hypothesis. And it was possible to check each one of them through the formula Conclusions were established where industrial safety minimizes the risks of accidents during the teaching-learning process. In addition, there is ignorance in the 100% of the population surveyed on the use of the computer. Recommending that teachers and administrative staff apply rules that they play with the correct use of technological equipment.